Management of skin and soft-tissue infections and acne with topical nadifloxacin: a comprehensive review - Muchhala, Snehal; Sarkar, Rashmi; Lahiri, Koushik; Kharkar, Rajendra D.; Rathod, Rahul (International Journal of Research in Dermatology, 2022)
Skin and soft tissue infections (SSTIs) and acne are multi-factorial skin conditions that involve microbial invasion of the skin and underlying soft tissues; though, both have different pathogenesis. Most of these infections are caused by bacteria, affecting all age groups. Early diagnosis and appropriate antimicrobial therapy remain the cornerstone of management of SSTIs and acne. Over the years, an increase in antibiotic resistance has been reported with mupirocin and fusidic acid that makes the management of SSTIs and acne increasingly challenging. Further, these antibiotics are unable to penetrate biofilms and show their action on the microorganisms embedded deep in the polymeric matrix. In this review, we have discussed the current evidence on the efficacy and safety profile of nadifloxacin compared to other currently available antimicrobial agents. An extensive search was performed through PubMed and Medline using relevant key words. This article has highlighted nadifloxacin’s broad antimicrobial spectrum, unique dual mechanism of action, distinct characteristics like ability to retain efficacy in acidic pH, low antibiotic resistance and superior action against biofilms. This review concludes that nadifloxacin, could be a potential empirical therapy in the management of SSTIs and acne.